The adoption and abolition of the local developmentexaction system by the city of Yokohama - Taguchi, Toshio (International Planning History Society Proceedings, 2018)
This thesis intends to explore the rationale behind the adoption and abolition of Yokohama’s local development exaction system (“LDE system”). LDE systems were independently and locally formulated by local governments in response to challenges they faced across Japan, and Yokohama provides a leading example of a functional LDE system pursuant to which land developers were required to donate land for public use as a condition of their receiving development approval from the city government. Ichio Asukata, the socialist mayor at the time of the LDE system’s introduction, invited Akira Tamura, a planner, to the city administration to solve the town planning issues. Japan’s new Town Planning Act of 1968 did not contain provisions authorising the exaction of land. Therefore, Yokohama became the first large city to adopt an LDE system in 1968. The LDE system was used as an administrative guideline which ran the risk of legal challenge by affected developers. After Asukata’s term in office, a succession of conservative mayors narrowed and reduced the obligations imposed under the LDE system and finally ended its use in 2004. This study presents some idea of how local initiatives can be implemented independently by local governments in a highly constrained fiscal environment without any support from the central government.